(untitled) (Indian Journal of Animal Production and Management, 2013)
An investigation was undertaken with 55 units of poultry farmers and farm units for evaluation of small scale farm economics of 3 types of chicken i. e. Rhode Island Red (RIR), Vanaraja and Local (non descript) under 3 systems of rearing viz. intensive deep litter, semi intensive and improved free range system located at Deptt. of LPM, Kolkata; Namkhana & Gosaba block of South 24 parganas, West Bengal. Small scale farm economics were calculated in terms of Benefit Cost Ratio (BCR). It was observed that in the intensive deep litter system of management there was chance of loss in case of Local (non-descript) farming but it was comparatively beneficial for both of RIR and Vanaraja farming. Among them RIR birds showed good result (0.14±0.05) than Vanaraja (0.05±0.05) on BCR. In case of semi-intensive system of management it was revealed that Vanaraja birds were performed better (0.34±0.05) than RIR (0.16±0.05) and Local (0.10±0.04). In case of improved free range system Vanaraja birds also were performed good (0.47±0.05) than Local (0.38±0.03) and RIR (0.24±0.05). The BCR of 3 farming systems (0.094±0.033, 0.201±0.024 and 0.363±0.024) in intensive deep litter, semi intensive and improved free range system respectively were significantly (P<0.05) variable but between birds it was revealed that the Local birds (0.238±0.024) were non-significant to Vanaraja (0.286±0.026) & RIR (0.181±0.027) but BCR of both RIR & Vanaraja were significantly (P<0.05) different to each other.